Managing R&D by normative scenarios. (22nd August 2005) - Edelmann, Jan; Bergman, Jukka; Jantunen, Ari
This study introduces a model of how to manage research and development work based on normative scenarios enabling the analysis of complex ideas and the recognition of new opportunities under high uncertainty. To visualise the concept of normative scenario, a case study is presented where the management of an organisation had an idea of radically changing wood procurement in the Finnish paper industry. A model for a normative scenario is presented on the basis of the case and the factors derived from it. The case is retrospectively analysed to show how normative scenarios could help firms to sense and seize innovative ideas that are strategic in nature. With the normative scenario process, strategic decision makers can find guidelines for critical timing questions by combining scenario techniques, real options thinking and the dynamic capability approach.